2017
DOI: 10.1007/978-3-319-58667-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Metrics for Energy-Aware Software Optimisation

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.For more information, please contact the WRAP Team at: wrap@warwick.ac.uk Metrics for Energy-Aware Software OptimisationStephen I. Roberts, Steven A. Wright, Suhaib A. Fahmy, and Stephen A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In our previous work, we have shown that metrics originating from the hardware community are not suitable for measuring software performance. We subsequently proposed two new dimensionless metrics that are designed to support energy-aware performance optimisation [34]. In this article, we provide derivations for POSE using both of these metrics, namely Energy-Delay Sum (EDS, Equation (1)) and Energy-Delay Distance (EDD, Equation 2):…”
Section: Energy-aware Metricsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we have shown that metrics originating from the hardware community are not suitable for measuring software performance. We subsequently proposed two new dimensionless metrics that are designed to support energy-aware performance optimisation [34]. In this article, we provide derivations for POSE using both of these metrics, namely Energy-Delay Sum (EDS, Equation (1)) and Energy-Delay Distance (EDD, Equation 2):…”
Section: Energy-aware Metricsmentioning
confidence: 99%
“…POSE is metric agnostic and is compatible with all members of the Et n family, the EDS and EDD metrics [34], and indeed any metric that is an element-wise monotonic function of runtime and energy consumption. The only prerequisites are that runtime and energy consumption can be accurately measured or calculated for the target platform.…”
Section: The Power Optimised Software Envelope Modelmentioning
confidence: 99%
See 3 more Smart Citations